The Role of Professionalism as a Mediator of the Influence of Emotional Intelligence and Perceived Organizational Support on Employee Performance - Lara, Lara; Lianto, Lianto; Ginting, Sunardi (Amkop Management Accounting Review (AMAR), 2025)
This study aims to explore and confirm the role of professionalism as a mediator of the influence of emotional intelligence and perceived organizational support on employee performance at the Human Resources Development and Personnel Agency in Landak Regency. The research method used in this study is the associative research method. The sampling technique used was saturated sampling involving 62 respondents. The data collection technique employed a questionnaire. The data collected were processed using SEM (Structural Equation Modeling) with WarpPLS 7.0 software. This study found that emotional intelligence did not have a significant effect on employee performance, perceived organizational support had a significant effect on employee performance, emotional intelligence had a significant effect on professionalism, organizational support had a significant effect on professionalism, and professionalism had a significant effect on mediating the relationship between emotional intelligence and perceived organizational support on employee performance